1988
DOI: 10.1111/j.1469-185x.1988.tb00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Determination and Sex Differentiation in Malaria Parasites

Abstract: Summary 1. The most coherent body of information on the malarial life‐cycles comes from studies on P. berghei and P. falciparum. For both species there is an extensive and accurate description of the life‐cycle available based on synchronized in‐vitro and in‐vivo infections (the latter only for P. berghei). 2. The trophozoites preceding the young gamonts are already sexually differentiated, that is, they are micro‐ and macrogamontoblasts. They are, however, morphologically indistinguishable from the asexual tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…The ploidy and replication of the gametocyte genome has been a controversial topic, resolved in large part by the studies of Cornelissen and Janse in the 1980s, who, using cytochemical techniques, showed that mature gametocytes like the merozoite are haploid, and that the male cell replicated its DNA three times in brief period (∼10 min) between induction and microgamete release – exflagellation (Janse et al ., 1986a,b; Cornelissen, ). This replication is cdpk4 dependent (Guttery et al ., ).…”
Section: Sexual Development In Mosquitomentioning
confidence: 99%
See 1 more Smart Citation
“…The ploidy and replication of the gametocyte genome has been a controversial topic, resolved in large part by the studies of Cornelissen and Janse in the 1980s, who, using cytochemical techniques, showed that mature gametocytes like the merozoite are haploid, and that the male cell replicated its DNA three times in brief period (∼10 min) between induction and microgamete release – exflagellation (Janse et al ., 1986a,b; Cornelissen, ). This replication is cdpk4 dependent (Guttery et al ., ).…”
Section: Sexual Development In Mosquitomentioning
confidence: 99%
“…Although this observation is entirely consistent with the absence of histone 1 from the genome, it also raises fascinating questions as to how the initial 14, and final 112, filamentous chromosomes (whose telomeres are likely embedded in the nuclear envelope) can be moved by the kinetochores on the spindle microtubules with such speed and precision without breaking. The female gamete like the originating immature female gametocyte is haploid, but the intervening nuclear events are unclear; data suggested that the DNA content may rise above 1°C (Cornelissen, ) and descriptions of spindle‐like structures in the developing (putative) macrogametocyte are either erroneous or suggest the female genome is somehow modified (Sinden et al ., ).…”
Section: Sexual Development In Mosquitomentioning
confidence: 99%
“…The fact that both female and male can be produced by haploid bloodstage parasite, the sex of a gametocyte does not result from chromosomal differences between both types of cell but their development must be due to selective gene expression. In general, the number of female gametocytes predominates over the number of male, but this predominance may vary at different times between cloned infections (Cornelissen 1988, Schall 1989.…”
Section: Development Of Gametocytes (Gametocytogenesis)mentioning
confidence: 99%
“…Effects of PMA on gametocyte in petri dish cultures each holding 1.5 ml medium and 150 p1 of 50% red cell suspension with an initial parasitemia of 0.4%. Each dish was sampled on day 5 Table 2. EtOH-50,000 corresponded to the ethanol introduced with PMA at 20 ng/ml, and EtOH-20,000 to that introduced with PMA I, Means for the 3 dishes with standard deviation.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…falciparum this was shown when the 1 st microscopically isolated clones of this species were grown up in culture and found to produce gametocytes of both sexes [29]. It follows that a single erythrocytic merozoite must contain in its haploid genome the information for both sexes of gametocytes as well as for the asexually reproducing forms [5]. Environmental signals must then determine the pathway of differentiation [9].…”
mentioning
confidence: 96%